Anaesthetic choice for hip or knee arthroplasty in New Zealand: Risk of postoperative death and variations in use. Issue 3 (May 2022) - Gurney, Jason K; McLeod, Melissa A; Campbell, Douglas; Dennett, Elizabeth; Jackson, Sarah; Koea, Jonathan; Lash, Nicholas; Ongley, Dick
Anaesthetic choice for large joint surgery can impact postoperative outcomes, including mortality. The extent to which the impact of anaesthetic choice on postoperative mortality varies within patient populations and the extent to which anaesthetic choice is changing over time remain under-explored both internationally and in the diverse New Zealand context. In a national study of 199, 211 hip and knee replacement procedures conducted between 2005 and 2017, we compared postoperative mortality among those receiving general, regional or general plus regional anaesthesia. Focusing on unilateral ( n =86, 467) and partial ( n =13, 889) hip replacements, we assessed whether some groups within the population are more likely to receive general, regional or general plus regional anaesthesia than others, and whether mortality risk varies depending on anaesthetic choice. We also examined temporal changes in anaesthetic choice over time. Those receiving regional alone or general plus regional for unilateral hip replacement appeared at increased risk of 30-day mortality compared to general anaesthesia alone, even after adjusting for differences in terms of age, ethnicity, deprivation, rurality, comorbidity, American Society of Anesthesiologists physical status score and admission type (e.g. general plus regional: adjusted hazard ratio (adj. HR)=1.94, 95% confidence intervals (CI) 1.32 to 2.84). By contrast, we observed lower 30-day mortality among those receiving regional anaesthesia alone compared to general alone for partial hip replacement (adj. HR=0.86, 95% CI 0.75 to 0.97). The latter observation contrasts with declining temporal trends in the use of regional anaesthesia alone for partial hip replacement procedures. However, we recognise that postoperative mortality is one perioperative factor that drives anaesthetic choice.